Pengembangan Management Information System Berbasis Laravel untuk Optimasi Produktivitas Karyawan PT.XYZ - Vega, Laurentius Dika Andreano; Pratama, Arnoldus Julio; Hermawan, Latius (Universitas Multi Data Palembang, 2025)
Unorganised employee data management can hamper the company's operational efficiency and increase the risk of recording errors. This research develops a Laravel 11-based Employee Data Management System to overcome these problems. Laravel 11 was chosen because of its scalable and efficient architecture in modern web application development. The system was designed using the Rapid Application Development (RAD) method to accelerate the development process through iteration and continuous feedback. A MySQL database was used to ensure efficient data management. This web-based system allows administrators to record, access, and analyse employee data in real-time with a higher level of accuracy. Test results show that the system improves data management efficiency, reduces recording errors, and increases transparency in human resource management. With this system, companies can optimise productivity and support data-driven decision-making.